ETHNOMATHEMATICS: EXPLORATION IN KAJANG LAKO HOUSE - Elda Rahmadhana; Yulyanti Harisman (Universitas Swadaya Gunung Jati., 2023)
This study aims to identify and describe the mathematical concepts contained in the Kajang Lako Jambi House. This research is a qualitative research using an ethnographic approach. The instruments used in this study were humans as the main instrument, observation guidelines, interview guidelines, documentation, and field notes. Collecting data in this study using observation, interviews, documentation, and field notes. Data analysis techniques were carried out by data reduction, data presentation, and Conclusion Drawing/Verification of Data. The results of this study describe the architectural design of Kajang Lako Jambi House. In the architecture of the Kajang Lako Jambi House, many geometric shapes are applied, including the heads of the stairs on the Kajang Lako Jambi House stairs in the form of cubes, handrails on the stairs, krawo, and Jambi traditional aisle chairs in the house in the form of blocks, the roof of the house as a whole is in the form of triangular prisms, the roof Jambi traditional aisles are in the form of a rectangular pyramid, square windows, doors, carved frames, and the sloping sides of a rectangular roof, then a roof covering called tedeng/tebarlayar which is triangular in shape. Apart from that, the counting of the steps on the steps of the Kajang Lako House applies the concept of a number pattern, as well as the carvings on the house, doors and window screens using the concept of reflection. These are all mathematical concepts that can introduce mathematics learning through local culture.Keywords: Ethnomathematics, Mathematics, Kajang Lako House